On φ-Concircularly Symmetric Kenmotsu Manifolds: Uday Chand De, Krishnendu De - Team, Support (Thai Journal of Mathematics, 2012)
We study locally and globally φ-concircularly symmetric Kenmotsu manifolds. At first we show that in a Kenmotsu manifold globally φ-symmetry and globally φ-concircularly symmetry are equivalent. Next we study 3-dimensional locally φ-concircularly symmetric Kenmotsu manifolds. Finally, we give some examples of φ-concircularly symmetric Kenmotsu manifolds.